Traditional Medicinal Plant Practices of the Baram People in Gorkha, Nepal - Devkota, Balak; Acharya, Usha (Journal of Indigenous Knowledge and Practice, 2025)
The Baram people, a marginalized ethnic group in Nepal, rely significantly on these plants for healthcare, yet the specific medicinal plant practices remain underexplored. The purpose of this study is to explore the medicinal plants used by the Baram people in Gorkha District, focusing on their applications in treating various health problems. We employed ethnographic method with semi-structured interviews, observations and focus group discussions. The findings of the study listed 112 medicinal plant species from 47 plant families used by the Baram people to treat 41 distinct health conditions, and the most commonly treated health problems: heat stroke, cough, gastritis, and stomach problems. The study underscores the importance of preserving both the plant species and the indigenous knowledge that sustains them, as they are essential to the Baram’s cultural identity and survival, as well as promoting sustainable use of natural resources for both ecological and economic benefits.